IBN ARABI AND FRITHJOF SCHUON’S ANDROCENTRIC ONTOLOGY - Cennet Ceren Cavus (Felsefe Dünyası)
Ibn Arabi’s philosophy has been addressed by some scholars as a source of Islamic feminism because of his revolutionary ideas and practices concerning women. In his ontology, he consecrates femininity by putting the feminine Essence (dhât) at the top of his existential hierarchy. Frithjof Schuon, who reads Ibn Arabi’s philosophy very critically, refers to the feminine aspect of God with the concept of “Eternal Feminine”. At the first sight, both thinkers seem to have very egalitarian perspectives in terms of gender relations. However, are their ontologies really pro-feminine? This paper discusses the two Sufis’ understandings of femininity, masculinity, and “God’s femininity” in detail with a critical method. I argue that by adopting the ancient “active man-passive woman” discourse Ibn Arabi and Schuon construct their ontologies on the feminine-masculine dichotomy and establish a hierarchy to the detriment of femininity. In dichotomies they elaborated to explain their metaphysics -such as “active-passive”, “total-part”, “superior-inferior”, and “essence-accident”-, they attribute all the favorable sides to the masculinity while attributing the unfavorable sides to the femininity. Moreover, Ibn Arabi puts men in the place of God in their relation to women while Schuon regards men as the image of God’s totality, not women. Therefore, even though they have some discourses consecrating femininity, their ontologies are quite pro-masculine since they sustain the actual androcentric approach to sex.